Analisa Yuridis Potensi Overlapping Antara Merk Tiga Dimensi (Three Dimensional Marks) dengan Desain Industri dalam Hukum Hak Kekayaan Intelektual - Xavier Nugraha; Ezra Tambunan (Fakultas Hukum Universitas Islam Indonesia, 2020)
One of the things that can make it easier for consumers to be able to distinguish products from one another is the presence of a brand that is a marker of the existence of a product. In this case the Law No. 15 of 2001 concerning brands, precisely in Article 1 describes the definition of the brand itself as a sign in the form of images, names, words, letters, numbers, color arrangements, or a combination of these elements which has a distinguishing power and is used in trade or service activities. As time goes on and the development of technology increases, new concepts are called non-traditional marks or non-traditional brands. These non-traditional brands are further divided into two types, namely non-traditional visual brands (including three-dimensional brands, colors, holograms, slogans, film and book titles, multimedia signs, positions, and gesture) and non-visual non-traditional brands (including sounds, aroma, taste, and texture). Speaking about the Three Dimensional Brands in Indonesia, it turns out that there is no clear concept regarding the Three-Dimensional Brand itself even though in Law No. 20 of 2016 replaced the 2001 Trademark Law has provided protection for Three-Dimensional Brands as well as through the Law Minister Regulation and Ham (Pemenkuham) No. 67 of 2016 that Three-dimensional Brands can be registered. From this, the question arises,